Place-Based Randomized Trials to Test the Effects on Instructional Practices of a Mathematics/Science Professional Development Program for Teachers. - Porter, Andrew C.; Blank, Rolf K.; Smithson, John L. (Annals of the American Academy of Political & Social Science, 2005)
Part of a special issue on place randomized trials in public policy. The writers describe a professional development model that was designed for and is being tested in around 50 middle schools in five large urban districts. They describe the successes and failures of treatment implementation and the collection of baseline and outcome data and highlight lessons that can be learned about using place-based randomized trials to test the efficacy of education programs.